Modulation of Trypanosoma cruzi-specific T-cell responses after chemotherapy for chronic Chagas disease - Albareda, María Cecilia (2015)
Fil: Albareda, María Cecilia. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.